Ferroelectric polarization-enhanced photocatalytic properties and photo-induced charge carrier behavior of Au/BaTiO3 - Chao, Chunying; Zhou, Yiping; Han, Tianli; Yang, Yanyan; Wei, Jiyu; Li, Hao; He, Weiwei (Journal of alloys and compounds, 2020)
Single-crystal heterostructured Au/BTO nanoparticles were fabricated successfully through a simple hydrothermal process. The prepared heterostructured nanoparticles were characterized by XRD, SEM, HRTEM, UV–vis adsorption spectroscopy and XPS. Results display that Au nanoparticles with the size of ∼5 nm loaded on the surface of the ferroelectric tetragonal phase BTO nanoparticles. The heterostructured photocatalyst showed an enhanced photocatalytic activity toward the degradation of RhB under UV light irradiation. Transient photovoltage (TPV) spectra results demonstrated that the pure BTO and Au/BTO 5.0 wt% show negative TPV signal. Moreover, TPV results demonstrated that the Au loading boosted the separation and transmission of photoinduced carriers under UV light. Furthermore, the ferroelectric polarization not only promoted the fast separation of photogenerated carriers but also prolonged the carrier lifetime. These all enhanced the photocatalytic performance. [Display omitted] •Heterostructured Au@BaTiO3 nanoparticles were prepared by a hydrothermal process.•Heterostructured Au@BaTiO3 nanoparticles displayed a superior UV-light activity caused by the ferroelectric nature.•Au act as electron traps rather than generators of the photoexcited electrons.•Au boosts the separation and transmission of photoinduced carriers.